2019
DOI: 10.1101/mcs.a003665
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional responders with invasive mucinous adenocarcinomas: a phase 2 trial of bortezomib in patients with KRAS G12D-mutant lung cancers

Abstract: KRAS G12D-mutant/p53-deficient non-small-cell lung cancer (NSCLC) models are dependent on the NF-κB pathway that can be down-regulated by the proteasome inhibitor bortezomib. Two exceptional responders were observed on prior clinical trials of bortezomib, both of whom had KRAS G12D-mutant NSCLC, prompting the initiation of this single-center phase 2 trial. Patients with advanced KRAS G12D-mutant NSCLC were eligible. Bortezomib was administered at 1.3 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
4
21
0
Order By: Relevance
“…Dose‒response confirmatory screening provided further evidence for a panel of compounds that inhibit the KRAS G12D organoid growth, raising the possibility of KRAS G12D -dependent targets or pathways. Our results support the recent clinical trial of bortezomib in non-small cell lung cancer with two exceptional responders, both of whom had KRAS G12D mutant tumors ( Drilon et al., 2019 ). We also confirmed two proteasome inhibitors, carfilzomib and MLN9708, which potently inhibit the growth of KRAS G12D organoids.…”
Section: Discussionsupporting
confidence: 90%
“…Dose‒response confirmatory screening provided further evidence for a panel of compounds that inhibit the KRAS G12D organoid growth, raising the possibility of KRAS G12D -dependent targets or pathways. Our results support the recent clinical trial of bortezomib in non-small cell lung cancer with two exceptional responders, both of whom had KRAS G12D mutant tumors ( Drilon et al., 2019 ). We also confirmed two proteasome inhibitors, carfilzomib and MLN9708, which potently inhibit the growth of KRAS G12D organoids.…”
Section: Discussionsupporting
confidence: 90%
“…114 Another study in which patients were selected based on KRAS G12D mutation status also showed one exceptional responder with 66% tumor regression. 115 The authors later evaluated the p53 status of these patients based on preclinical in vivo studies showing increased response to proteasome inhibitors in a p53 null background compared to wild-type. Results were available in only 9 out of 22 patients due to tissue availability, and as a further caveat, p53 status was assessed by immunohistochemistry (IHC), which is at best, an imperfect correlate for p53 mutational status with a significant rate of both false positivity and negativity.…”
Section: Crosstalk Between Mutant P53 and The Proteasome Machinerymentioning
confidence: 99%
“…In fact, the screens have been notable for little or no target overlap between their results, with the exception of proteosome-related genes [ 58 ]. Bortezomib, a proteosome inhibitor, was associated with modest anti-tumor activity and durable disease control in a small fraction of patients with KRAS G12D mutant lung tumors [ 63 , 64 ]. However, KRAS G12D mutation alone is not a robust predictor of response and further evaluation should only be performed after elucidation of co-mutations and histologic subtype that may predict therapy sensitivity [ 63 , 64 ].…”
Section: Treatment Failures Of the Past In Mutant Kras mentioning
confidence: 99%